Importance of ERK1/2 in Regulation of Protein Translation during Oocyte Meiosis - Kalous, Jaroslav; Tetkova, Anna; Kubelka, Michal; Susor, Andrej (International journal of molecular sciences, 2018)
Although the involvement of the extracellular signal-regulated kinases 1 and 2 (ERK1/2) pathway in the regulation of cytostatic factor (CSF) activity; as well as in microtubules organization during meiotic maturation of oocytes; has already been described in detail; rather less attention has been paid to the role of ERK1/2 in the regulation of mRNA translation. However; important data on the role of ERK1/2 in translation during oocyte meiosis have been documented. This review focuses on recent findings regarding the regulation of translation and the role of ERK1/2 in this process in the meiotic cycle of mammalian oocytes. The specific role of ERK1/2 in the regulation of mammalian target of rapamycin (mTOR); eukaryotic translation initiation factor 4E (eIF4E) and cytoplasmic polyadenylation element binding protein 1 (CPEB1) activity is addressed along with additional focus on the other key players involved in protein translation.
Keywords: fosfatidylinositol-3-kinasy; Protein Binding; RNA, Messenger; oocyty; vývojová regulace genové exprese; mTOR; Eukaryotic Initiation Factor-4E; Gene Expression Regulation, Developmental; CPEB1; signální transdukce; Protein Biosynthesis; proteosyntéza; Mitogen-Activated Protein Kinase 3; TOR serin-threoninkinasy; Meiosis; Phosphatidylinositol 3-Kinases; polyadenylace; MAP kinase; oocyte; Signal Transduction; mRNA Cleavage and Polyadenylation Factors; TOR Serine-Threonine Kinases; vazba proteinů; meióza; Polyadenylation; Animals; eukaryotický iniciační faktor 4E; cytoplazma; lidé; faktory štěpení a polyadenylace mRNA; Cytoplasm; ERK1/2; Mitogen-Activated Protein Kinases; Humans; zvířata; translation; mitogenem aktivovaná proteinkinasa 3; eIF4E; mitogenem aktivovaná proteinkinasa 1; mitogenem aktivované proteinkinasy; messenger RNA; Mitogen-Activated Protein Kinase 1; Oocytes